Tetrahydrobiopterin supplementation reduces atherosclerosis and vascular inflammation in apolipoprotein E-knockout mice. - Schmidt, T; McNeill, E; Douglas, G; Crabtree, M; Hale, AB; Khoo, J; O'Neill, C; Cheng, A; Channon, K; Alp, N (2010)
BH4 (tetrahydrobiopterin) supplementation improves endothelial function in models of vascular disease by maintaining eNOS (endothelial nitric oxide synthase) coupling and NO (nitric oxide) bioavailability. However, the cellular mechanisms through which enhanced endothelial function leads to reduced atherosclerosis remain unclear. We have used a pharmaceutical BH4 formulation to investigate the effects of BH4 supplementation on atherosclerosis progression in ApoE-KO (apolipoprotein E-knockout) mice. Single oral dose pharmacokinetic studies revealed rapid BH4 uptake into plasma and organs. Plasma BH4 levels returned to baseline by 8 h after oral dosing, but remained markedly increased in aorta at 24 h. Daily oral BH4 supplementation in ApoE-KO mice from 8 weeks of age, for a period of 8 or 12 weeks, had no effect on plasma lipids or haemodynamic parameters, but significantly reduced aortic root atherosclerosis compared with placebo-treated animals. BH4 supplementation significantly reduced VCAM-1 (vascular cell adhesion molecule 1) mRNA levels in aortic endothelial cells, markedly reduced the infiltration of T-cells, macrophages and monocytes into plaques, and reduced T-cell infiltration in the adjacent adventitia, but importantly had no effect on circulating leucocytes. GCH (GTP cyclohydrolase I)-transgenic mice, with a specific increase in endothelial BH4 levels, exhibited a similar reduction in vascular immune cell infiltration compared with BH4-deficient controls, suggesting that BH4 reduces vascular inflammation via endothelial cell signalling. In conclusion, BH4 supplementation reduces vascular immune cell infiltration in atherosclerosis and may therefore be a rational therapeutic approach to reduce the progression of atherosclerosis.